The Impact Of Production Cost Efficiency, Dividend Policy, And Capital Structure On The Growth Of Equity Of Automotive And Component Companies On The Indonesia Stock Exchange 2020-2024 - Manurung, Indah Permata Maria Br; Rahmaniar , Mutiara (Journal of Industrial Engineering & Management Research, 2026)
This study aims to analyse the influence of production cost efficiency, dividend policy and capital structure on the growth of equity capital in companies in the automotive and components sector listed on the Indonesia Stock Exchange for the period 2020–2024. This study employs a quantitative approach using the panel data regression method. The population of this study consists of 26 companies in the automotive and components sector, with a sample of 20 companies. The sample was selected using a purposive sampling technique. The data used are secondary data from the companies’ annual financial reports, processed using EViews 12 software. The results of the empirical tests reveal that production cost efficiency has a negative and significant influence on equity growth, that dividend policy has no significant influence on equity growth, whilst capital structure has a positive and significant influence on equity growth. The results of the simultaneous test (F-test) show that production cost efficiency, dividend policy and capital structure, taken together, have a significant influence on equity growth. This study supports the pecking order theory, the dividend irrelevance theory and the trade-off theory in explaining the determinants that influence the growth of companies’ equity.